Morphometric discrimination in Bali cattle (Bos javanicus) at two different altitude areas of Jambi province, Indonesia - DEPISON, DEPISON; PUTRA, WIDYA PINTAKA BAYU; H, DIKA IRMAYA (The Indian Journal of Animal Sciences, 2022)
Bali cattle (Bos javanicus) is an important livestock for the farmers at Jambi Province of Indonesia for meat production purposes. This research was aimed to classify adult Bali cattle (about 3.5 years age) based on their body measurements (morphometrics). The animals in this study were collected from two different altitude areas (lowland and midland) of Jambi province. A canonical discriminant analysis (CDA) was computed in this study for discrimination of animals. A total of 480 animals collected from lowland (180 animals) and midland (300 animals) areas were used in the present study. Thus, seven (7) morphometrical measurements of body length (BL), withers height (WH), chest girth (CG), chest depth (CD), shoulder width (SW), canon circumference (CC) and rump height (RH) were measured in each animal. Research showed that four (4) body measurements, viz. BL, CG, SW and RH were described as the discriminating variables with a canonical correlation of 0.83 (very high). In conclusion, about 90% of Bali cattle at lowland and midland areas could be classified using body measurements.